How does introduction of strategic job in four and five star hotels affect organizational commitment and organizational citizenship behaviour: A theoretical framework - Ahmad, Rozila; Solnet, David (2008)
The objective of the study is to discuss HR practices system variation within the hotel industry related to the identification of strategic jobs, and how this influences employees’ work attitudes.The context for this research is four and five star hotels in Malaysia.This paper provides an integrated framework and five research issues relating the concepts of the HR practices system, strategic and supporting jobs, affective organizational commitment and organizational citizenship behaviour.With efficient utilization of internal resources and effective allocation of human capital investment while ensuring positive job behavioural outcomes, the theoretical framework is useful in improving the effectiveness of HR practices system and may serve as a guide to practitioners.This study contributes to SHRM theory through closer examination of the strategic job concept and investigation of applying more than one HR practices system in an establishment on employees’ behaviour.